Investigation of surface textures deterioration on pavement skid-resistance using hysteresis friction models and numerical simulation method - Haoyuan Luo; Siyu Chen; Leyi Zhu; Xiyin Liu; Yangzezhi Zheng; Runming Zhao; Xiaoming Huang (Friction, 2023)
Abstract Many rubber friction theories or some method combined theories and field-experiments are employed to evaluate the pavement skid-resistance deterioration due to the evolution of surface textures. However, these methods are difficult to be implemented in the analysis of situations with multi-factor coupling and some extreme conditions. This study developed a framework to evaluate the skid-resistance deterioration of asphalt pavements. In this framework, the portable laser scanning was used to create the digital worn pavement model, and a hydroplaning finite element (FE) model for these digital worn pavements was constructed to evaluate coupling effects of the texture evolution and factors of slip ratio, slip angle, velocity and water film on braking-cornering characteristics of tire. In this study, the deterioration of skid-resistance of five typical asphalt pavements due the surface texture wear was systematically investigated by this framework. Compared with previous works, this study established the rubber friction models for each digital worn pavement considering the energy hysteresis of rubber and the power spectrum density of surface texture. And the rubber friction model was used to define the interaction behaviors between the tire and corresponding wore pavements in the FE hydroplaning model, rather than using an empirical friction model or a fixed friction coefficient.